Synthesis of graft copolymers onto starch and its semiconducting properties - Nevin Çankaya (Results in Physics, 2016)
Literature review has revealed that, although there are studies about grafting on natural polymers, especially on starch, few of them are about electrical properties of graft polymers. Starch methacrylate (St.met) was obtained by esterification of OH groups on natural starch polymer for this purpose. Grafting of synthesized N-cyclohexyl acrylamide (NCA) and commercial methyl methacrylate (MMA) monomers with St.met was done by free radical polymerization method. The graft copolymers were characterized with FT-IR spectra, thermal and elemental analysis. Thermal stabilities of the graft copolymers were determined by TGA (thermo gravimetric analysis) method and thermal stability of the copolymers is decreased via grafting. The electrical conductivity of the polymers was measured as a function of temperature and it has been observed that electrical conductivity increases with increasing temperature. The absorbance and transmittance versus wavelength of the polymers have been measured. Keywords: Starch, Graft copolymer, Semiconducting, Thermal stability, Starch methacrylate